2021
DOI: 10.1166/jno.2021.3140
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Concept: Free Energy Harvesting Through Self-Powered Triboelectric Nanogenerator

Abstract: Globally, the internet of things (IoT) is a concept for the realization, integration, and updating of both the physical and digital world through the use of sensors to obtain accurate data from the environment triboelectric nanogenerators (TENG) are shown to be promising for applications involving self-powered sensors and mechanical energy harvesting. Traditional triboelectric generators harvest energy in contact mood but are not cost-effective. Therefore, in this research article, we report on the design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…The hybrid composite is studied to predict water absorption and mechanical features with differing weight percent of fiber content [24]. It is also observed that the hybrid effect of fibers enhanced the overall performance and composite attributes [26,68]. Composite with two different fibers, used in the proportion of 25 percent Coir and 75 percent Kevlar, inculcated good impact, flexural, and water absorption properties.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The hybrid composite is studied to predict water absorption and mechanical features with differing weight percent of fiber content [24]. It is also observed that the hybrid effect of fibers enhanced the overall performance and composite attributes [26,68]. Composite with two different fibers, used in the proportion of 25 percent Coir and 75 percent Kevlar, inculcated good impact, flexural, and water absorption properties.…”
Section: Introductionmentioning
confidence: 98%
“…Some fibers like hemp, pineapple, sisal, and kenaf show similar properties compared to steel and aluminum [6,[57][58][59][60][61]. Because of the innumerable and positive characteristics of natural fibers, the utilization of composites made by these fibers shows their wide range of uses in areas of vehicle, construction, aircraft, and marine industries [7][8][9][10][11][62][63][64][65][66][67][68]. Despite these numerous pros of NFCs, some cons need to be observed, such as low impact strength, high rate of water absorption, and lower heating capacity.…”
Section: Introductionmentioning
confidence: 99%